The Comparison of the Effects of Electronic Education with Workshop Education on Knowledge of Nursing Students about Patient\'s Rights - Shokoh Varaei; Parisa Afshar Nasr; Naser Bahrani; Kameleh Mohamadi (مراقبت پرستاری و مامایی ابن سینا, 2018)
Introduction: Patient's rights are the communication rules  between patients, health staff, and health services.  There are concerns regarding observing the patient's rights including privacy and informed consent on the part of medical personnel. Therefore, the present study was conducted with the aim to compare electronic and workshop education on knowledge of nursing students about patients’ rights. Method: This is a semi- experimental study with two groups. 60 nursing students were chosen through simple-random method, and were allocated to electronic and workshop education groups. Educational content about privacy and informed consent were taught to students in a four-hour workshop. The very same content on a compact disk was taught to electronic group. Before and after educational intervention, the students' level of knowledge was assessed with questionnaires and data were analyzed with statistical-analytical tests and SPSS software. Results: The results showed that the mean level of knowledge in both groups was increased after intervention But in the workshop group it was statistically meaningful (P=0.001) Conclusion: Nursing students' training is a way to increase the respect for patient’s rights. However, achieving this goal requires educational approaches to provide learning infrastructures to make the nurses ready for patients' care taking  in the future.